Diseño arquitectónico de la Unidad Educativa Intercultural Bilingüe “El Cercado” - Isama Oña, Melany Denisse (2023)
The curricular integration work is carried out in the city of Cotacachi, in the community of 'El Cercado', which belongs to the Andean zone of the city. The research is given by the deterioration and shortage of space in the current Educational Unit of the sector, which forces the inhabitan ts of the community to leave the same, in search of a better educational development. Currently, the country's educational system is controlled by different regulatory entities. Initial education is guided by the Ministry of Economic and Social Inclusion ( MIES) and basic and high school education is guided by the Ministry of Education. In order to improve education in the sector, the design of the Intercultural Bilingual Educational Unit 'El Cercado' was implemented. Guided through a methodology in which a problem is defined, then there is a contextual review that helps to have a better approach to the site, an analysis of references that will contribute in the functional, formal and technical aspects, analysis of the regulations that will help establishing the necessary parameters at the time of design. Finally, an architectural proposal that will be the result of all the research is given.